PENANAMAN KARAKTER DALAM PEMBELAJARAN MATEMATIKA DI KELAS VII SMP ISLAM AL-ISHLAH BUKITTINGGI - Muhammad Imran; Aniswita (Universitas Pahlawan Tuanku Tambusai, 2022)
This research is motivated by the inculcation of character which is the school's vision, at Al-Ishlah Islamic Junior High School Bukittinggi. The school's vision reads,